Complexity and model comparison in agent based modeling of financial markets - Alexandru Mandes; Peter Winker (Philipps-University Marburg, School of Business and Economics, 2015)
Agent based models of financial markets follow different approaches and might be categorized according to major building blocks used. Such building blocks include agent design, agent evolution, and the price finding mechanism. The performance of agent based models in matching key features of real market processes depends on how these building blocks are selected and combined. For model comparison, both, measures of model fit and model complexity are required. Some suggestions are made on how to measure complexity of agent based models. An application for the foreign exchange market illustrates the potential of this approach.
Keywords: C63; C18; C58; G17; 330; agent based modeling; model selection; complexity